Batas Usia Minimal Wali Nikah dalam Aplikasi Simkah Perspektif Hukum Islam dan Hukum Positif - Zulfa Munawaroh; Syaiful Aziz; Rafida Ramelan (Journal of Sharia and Legal Science, 2024)
SIMKAH is an application used to document marriage information data. One important aspect in marriage registration is the role of the marriage guardian. However, with the absence of an age limit for the marriage guardian in the guardian entry in the SIMKAH application, marriage registration can be continued even though the guardian is very young, thus this study aims to analyze the provisions of the age limit for the marriage guardian in the guardian entry in the SIMKAH application based on the perspective of Islamic law and positive law. The research method used is library research with a normative legal approach, namely the collected data is analyzed with Islamic law regulations and positive law related to the age limit for the marriage guardian. The results of the study obtained are that the provisions of the minimum age limit for the marriage guardian in the Marriage Management Information System (SIMKAH) application are not limited and can even record the age of the marriage guardian of 10 years. Islamic law analysis recommends the use of the maslahah al-mursalah theory in determining the age of the marriage guardian, which ranges from 18-21 years. However, in the Positive Law Analysis, the provisions of the minimum age limit for marriage guardians in the SIMKAH application are not in accordance with the provisions of a person's maturity to be able to be responsible for carrying out legal acts contained in applicable laws. Although both have the same essence in regulating the purpose of marriage, they have different provisions on the age limit of maturity and the age limit of puberty.